ANALISIS LIKUIDITAS PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN SIDENRENG RAPPANG - Dahrul, Ardianti (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to analyze the extent of liquidity of Perusahaan Daerah Air Minum (PDAM) Kabupaten Sidenreng Rappang. The liquidity ratios used as analysis tools are the Current Ratio, Quick Ratio, and Cash Ratio. The method used is a descriptive quantitative method by using secondary data from financial statements from 2015-2019. The results show that the current ratio analysis and quick ratio for 2015 do not meet the liquidity standard. The percentage value of the Current Ratio is 46%. This figure is below the standard liquidity of 200%. The percentage value for the Quick Ratio is only 43%, which is below the liquidity standard of 150%. The liquidity value continued to improve in the following years. In 2019, the liquidity value reached 1058% (current ratio) and 1008% (quick ratio). At the same time, the Cash Ratio fluctuates, and the percentage value is ugly. This ratio has an average percentage below 100%. In 2015 it was only 3%, in 2016 it increased to 13%, in 2017, it increased by 76%, in 2018, it decreased to 24%, and in 2019 it decreased to a value of 17%. That the company cannot pay its short-term obligations using the Cash Ratio, especially for the year studied, namely 2015-2019.